FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KOTA PALEMBANG - Putri amelia, Dhea; Hartati, Sukmini; Armaini, Rosy (Jurnal Riset Terapan Akuntansi, 2024)
The research discussed aims to identify the impact of tax socialization, tax sanctions, and the quality of public services on motor vehicle taxpayer compliance in the city of Palembang. This research uses quantitative methods, namely the nature of the assessment discussed. This research study consisted of a population of 1,261,128 people, who were then selected from a sample of 100 individuals by applying the Accidental Sampling technique. The information needed is primary data collection, which will be compiled in the questionnaire. The methodology applied to the study discussed is descriptive statistical analysis. The study findings show that 1) Socialization has statistically significant and positive implications for taxpayer compliance. 2) Sanctions have statistically significant and positive implications for taxpayer compliance. 3) Service quality has a substantial and profitable impact on taxpayers. 4) Socialization, penalties and service quality have a significant and statistically positive impact on taxpayer compliance. Keywords: Taxpayer Compliance, Socialization, Sanctions, Service Quality.